EMPLOYING DECENTRING TO ASSESS QUALITY OF SERVICES AND ITS CONTRIBUTION TOWARDS SATISFACTION - Usman YOUSAF; Mohsin ALTAF; Majid Mehmood BAGRAM; Haroon HUSSAIN (Management & Marketing)
The higher education scenario in Pakistan has gone through tremendous changes and improvements in the last decade. Competition resulting from a sudden surge in the number of higher education imparting institutions and the active role of Higher Education Commission has increased the pressure on the universities to continuously enhance the quality of educational services being provided by them. The aim of the researchers in this endeavor is to employ decentering in order to assess the quality of services being provided by the universities. The study has used the SERVQUAL tool by Parasuraman, Zeithmal and Berry (1991) on a five point Liker scale in order to gauge the responses of the students. Analysis was conducted on a total of 156 valid questionnaires. The sample included the students of the top five HEC (Higher Education Commission) recognized universities in the twin cities of Islamabad and Rawalpindi. Data was analyzed using Pearson correlation and regression. Factor analysis was also carried out so as to classify the most important dimensions for the students with respect to higher education in Pakistan. Statistical analysis disclosed a positive and significant association between service quality and customer satisfaction. The factor analysis revealed that the most significant dimension with respect to the Pakistan’s higher education sector are the level of management support, responsiveness of the service providers and the adequacy of physical facilities. The study highlights the importance of treating students as valued customers as the competition in the industry along with the regulatory requirements of HEC as well. The service providers need to be provided adequate support and backing of the top management. The physical facilities and the infrastructure must also be adequate enough to meet the growing and ever changing demands of the industry. The current study is the first of its kind that covers the higher education imparting institutions in Pakistan. Further it is suggested that more and more such researchers be conducted periodically in the future with an increased sample size in order to assess quality.